1992
DOI: 10.1037/0022-0663.84.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Properties of attention during reading lessons.

Abstract: A study investigated the attention of 116 children in six second-and third-grade classrooms while they participated in four lessons involving progressively more difficult stories. Analysis of videotapes of the lessons revealed that the likelihood of a lapse of attention was highest during the first 15 seconds of attention episodes. Lapses in attention were more likely among second graders than among third graders, among boys than among girls, in low groups than in middle groups, and in middle groups than in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…That group level was not a factor is a startling result in the light of the powerful influence of group that has appeared in a whole series of studies dating back to Weinstein (1976;see also, e.g., Anderson et al, 1991). Indeed, in the companion study involving the same lessons as the present study, Imai et al (1992) found that group level had a very strong influence on the likelihood that children would become inattentive. Evidently, decisions about feedback are primarily an individual matter whereas attention is sensitive to aspects of group culture.…”
Section: Problem Word Student Attemptmentioning
confidence: 90%
See 2 more Smart Citations
“…That group level was not a factor is a startling result in the light of the powerful influence of group that has appeared in a whole series of studies dating back to Weinstein (1976;see also, e.g., Anderson et al, 1991). Indeed, in the companion study involving the same lessons as the present study, Imai et al (1992) found that group level had a very strong influence on the likelihood that children would become inattentive. Evidently, decisions about feedback are primarily an individual matter whereas attention is sensitive to aspects of group culture.…”
Section: Problem Word Student Attemptmentioning
confidence: 90%
“…Imai et al (1992) have shown, analyzing data from the same 72 lessons analyzed in this study, that the low groups were more inattentive than high groups and that an increase in story difficulty caused a decline in students' attentiveness. 1 The strongest finding from the Imai et al study was the precipitous decline in attention immediately following reading errors.…”
Section: Problem Word Student Attemptmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, altogether there were 72 lessons examined in the study (6 classrooms x 3 reading groups x 4 stories). Imai et al (1992) have analyzed the dynamics of attention during the same 72 lessons.…”
Section: Design and Materialsmentioning
confidence: 99%
“…The details of the process of estimating the factor scores can be found in Imai et al (1992). The comprehension factor was allowed to load on the MAT, IGAP, and teacher rating measure, as well as on the measure of passage reading time.…”
Section: Assessment Of Reading Levelmentioning
confidence: 99%